Knockdown of BAG3 synergizes with olaparib to kill ovarian cancer cells via repressing autophagy. (24th December 2020) - Wang, Kexin; Zheng, Jianhua
Abstract : This study aimed at expounding the synergistic effect of Bcl-2-associated athanogene 3 (BAG3) knockdown and poly ADP-ribose polymerase (PARP) inhibitor on ovarian cancer (OC) cells and the potential mechanism. Short hairpin RNA (shRNA) targeting BAG3 (sh-BAG3) was transfected into SK-OV-3 (SKOV-3 ;SKOV3) and A2780 cells, and western blot assay was used to detect transfection efficiency. Cell proliferation and apoptosis were detected by the cell counting kit-8 method, 5-Bromodeoxyuridine (BrdU) experiment and flow cytometry analysis, respectively. The expressions of apoptosis-related proteins Bax and Bcl-2, as well as the expressions of autophagy-related proteins LC3-I, LC3-II and Beclin-1, were examined by western blot assay. Additionally, the cells were treated with autophagy activator rapamycin to investigate whether the tumor-suppressive function of BAG3 knockdown+PARP inhibitor was dependent on autophagy. In this work, we demonstrated that BAG3 knockdown further sensitized OC cells to olaparib treatment, reducing cellular viability and promoting apoptosis. Both sh-BAG3 and olaparib decreased the expression of Beclin-1 and the LC3-Ⅱ:LC3-I ratio, and their synergism further inhibited the process of autophagy. However, the aforementionede effects were reversed after the cells were treated with rapamycin. Based on these results, we concluded that BAG3 knockdown synergizes with olaparib to kill OC cells in vitro by repressing autophagy.